Saline Solutions in the Treatment of Inflammatory Diseases of the Nasal Cavity in Children - Iu.V. Marushko; E.D. Moskovenko; E.Yu. Marushko (Zaslavsky O.Yu., 2016)
The article provides an review of researches on the effectiveness of the irrigation therapy in the diseases of the nasal cavity and paranasal sinuses. There are also considered the data on the effectiveness of Pshik spray in the complex treatment of acute rhinitis.